Asket und Eschaton: Das Endzeitbuch des Šubhalmaran von Kirkuk - Binder, Matthias (Göttinger Orientforschungen. Syriaca., 2014)
"Apostolic Church of the East" refers to the church that found its expansion and its own shape on the soil of the ancient Persian empire. The crisis years of the early 7th century represent a decisive phase in this development This study deals with the thesis that Šubhalmaran von Kirkuk, one of the bishops involved at the time, processed these events in his "Book of the End Times". This book (edited in 2004 by David J. Lane as "Book of Gifts", Part 6) is an ancient Syrian text that has been neglected for a long time and has now been scientifically processed for the first time. Within the study, the often contradicting chronicle is contrasted with its own interpretation of the religious and political starting point. Furthermore, the "Endzeitbuch" is placed in relation to contemporary monk reform and mysticism as well as apocalyptic and above all to the christological debate. The individual motifs of Antichrist and Elijah, the Bride Christ motif and the psychologizing depiction of hell are to be emphasized. Some previously unknown fragments are isolated, Below is an apocalyptic pseudo-Clementine text and a German translation is attached.